A study on smartphone addiction among secondary students : a case study in SMK Hamzah, Machang, Kelantan / Nabilah Ismail, Nurul Asyiqin Mohd Adnan and Siti Nur Madihah Mohd Amin - Ismail, Nabilah; Mohd Adnan, Nurul Asyiqin; Mohd Amin, Siti Nur Madihah (2019)
Lately, smartphone addiction among high school students are worrying. This study aimed to identify the most contributing factor of smartphone addicts among secondary school students in Machang, Kelantan based on gender, parent income and duration of smartphone used. This issue is selected because young people are now addicted to smartphone, especially students. The phenomena will lead the student to become addicted to it, affecting the students' academic performance, daily activities, and health of the students. A structured questionnaire was used to gather data from the students. A total of 300 questionnaires were administered to both female and male students in Sekolah Menengah Kebangsaan (SMK) Machang. Descriptive analysis and ordinal logistic regression were used for data analysis in this study. According to Smartphone Addiction Scale score, 105 (35%) were classified as likely smartphone addiction. Gender and duration of smartphone used were the contributing factors of smartphone addiction among students. Even so, the most contributing factor is the duration of smartphone used. This study suggests that students should reduce the intense use of a smartphone for smoothly doing their daily-life activities.